INTERPERSONAL COMMUNICATION RELATIONSHIP AND EMOTIONAL INTELLIGENCE WITH TEACHER ACHIEVEMENT MOTIVATION IN MTs STATE REGENCY OF LANGKAT - Wijaya, Candra; Daulay, Nurika Khalila; Sihotang, M. Ismail Tumbor (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study aims to determine the relationship between interpersonal communication and emotional intelligence with teacher achievement motivation at MTs Negeri Stabat Langkat Regency. The formulation of the problems posed in this study are: 1) Is there a relationship between interpersonal communication and teacher achievement motivation at MTs Negeri Stabat Kab. Depart? 2) Is there a relationship between emotional intelligence and teacher achievement motivation at MTs Negeri Stabat Kab. Depart? 3) Is there a relationship between interpersonal communication and emotional intelligence with teacher achievement motivation at MTs Negeri Stabat, district. Depart? The type of research used is quantitative using a correlational approach, namely research that seeks to see the relationship between variables. The study population was all teachers of MTs Negeri Kab. Langkat numbered 41 people. Because the population is 41 people, the entire population is used as a research sample and is called total sampling. Data were analyzed using data analysis techniques with multiple linear regression. After the research data were analyzed, the following results were obtained: 1) There is a positive and significant relationship between teacher interpersonal communication (X 1 ) and teacher achievement motivation (Y) at MTs Negeri Stabat with a strong correlation level at the correlation coefficient value of 0.717. Meanwhile, the value of the ridge strength that occurs between the two variables is 0.717 or 71.7%. 2) There is a positive and significant relationship between teachers' emotional intelligence (X 2 ) and achievement motivation (Y) at MTs Negeri Stabat with a strong correlation level at the correlation coefficient value of 0.704. While the value of the strength of the relationship that occurs between the two variables is 0.704 or 70.4%. 3) There is a positive and significant relationship between teacher interpersonal communication (X 1 ) and teacher emotional intelligence (X 2 ) with teacher achievement motivation (Y) at MTs Negeri Stabat at a correlation level of 0.717. Meanwhile, the value of the strength of the relationship that occurs between the two variables is 0.717 or 71.7%. Thus it can be concluded that there is a positive and significant relationship between interpersonal communication and teachers' emotional intelligence with teacher achievement motivation at MTs Negeri Stabat Kab. Leave. This means that the higher the interpersonal communication and emotional intelligence of the teacher, the better the achievement motivation of the teacher.